Efficacy of Posaconazole Prophylaxis for Fungal Disease in Hematology Patients Treated With Chemotherapy and Transplantation: An Open-Label, Prospective, Observational Study - Li, Weiyang; Xia, Fan; Zhou, Haixia; Qiu, Huiying; Wu, Depei; Ma, Xiao; Sun, Aining (Frontiers in Microbiology, 2020)
Background: Posaconazole (PCZ) is used prophylactically to prevent invasive fungal infections (IFIs) in patients with hematological malignancies. Objective: To evaluate the cut-off serum concentration of PCZ for successful IFI prophylaxis in Chinese subjects. Patients and Methods: A total of 74 patients treated with induction chemotherapy (n = 10) and allogeneic hematopoietic stem cell transplantation (HSCT) (n = 64), who received PCZ prophylactically as an oral suspension for > 7 days, were included in the study. Clinical, radiological, microbiological culture results and treatment responses were analyzed and drug concentration assays performed. Results: The overall incidence of possible, probable and proven IFIs was 13.5% (10/74), with 5 patients in the chemotherapy group and 5 in the HSCT group. The PCZ serum concentration in most patients (54/63) was in the range of 0.25 – 1.0 µg/mL and this concentration range was significantly associated with the success rate of PCZ prophylaxis. A cut-off value of 0.47 µg/mL can be considered as an evaluation index for PCZ prophylaxis. Taking a proton pump inhibitor (PPI) would reduce the PCZ blood concentration, but not affect the IFD breakthrough point. PCZ treatment for hematopoietic malignancy, or HSCT patients with a serum concentration of PCZ < 0.47 µg/mL, were risk factors for PCZ prophylaxis of IFIs, determined by univariable and multivariable regression analyses. Conclusions: The serum concentration of PCZ was related to the incidence of IFIs and a serum concentration of > 0.47 µg/mL is highly recommended to avoid IFIs after chemotherapy or HSCT.